Keefektifan Media Pembelajaran pada Hasil Belajar Pendidikan Agama Islam Selama Pandemi Covid-19 - Muthoharoh, Muthoharoh; Bermula, Renaldi (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2022)
ABSTRACT The COVID-19 pandemic forced learning activities at schools to be temporarily suspended, in which all students remained at home. In the end, it was quickly decided to study from home. This was initially a major issue in education, but over time, there was a development in learning media, specifically E-learning, which became a learning medium used from the pandemic to the post-pandemic. This study aims to determine the effect and effectiveness of using e-learning media in Wahidin Middle School, Cirebon City. This study uses a quantitative method with the design of the One Group Pretest and Posttest Design. Data collection techniques include observation, tests, questionnaires, and documentation. The results of this study indicate PAI learning using e-learning media has an effect on student learning outcomes with the average score between the experimental class and the control class being 80.50 > 79.67. The use of E-Learning media in PAI subjects is effective on student learning outcomes as indicated by Mann Whitney test results, where the probability value of Asymp. Sig. (2-tailed) of 0.000 < 0.05, which means that there is a significant difference in student learning outcomes when using e-learning.